Autocitarsi in musica. Bach e l'arte della parodia - Raffaele Mellace (Parole Rubate, 2014)
A systematic intra-authorial intertextuality is typical of Johann Sebastian Bach's output. This distinctive operation represents a crucial strategy for the realization of some of his most important projects, such as the Mass in B Minor, the Oratorios and the Markus-Passion. This article offers an outline of Bach's (parodic) use of quotation in his instrumental and vocal works. This latter part of his production is of particular interest because it includes verbal texts and their inevitably complex semantic implications.